Reforma a la Ley Orgánica de Educación Superior en relación a su sistema de admisión, para garantizar el acceso a la educación superior en igualdad de oportunidades - Baños Aguilar, Efrain Vicente (2015)
The legal issues regarding this investigation is aimed at legal analysis of the regulatory arrangements in the Law on Higher Education and in relation to their intake system; Our Constitution of the Republic in its Section 1 states that Ecuador is a state constitutional rights and social justice, this designation is not a simple term or a simple statement, it is a change in vision and perception related importance and primacy have all the rights of a fundamental nature recognized not only by the Constitution but also by international human rights treaties; From this perspective, the principle of universal rights are characterized as intangible, inalienable, interdependent and can not be subject to reduction or restriction in any sphere or public or private. In the case of the right to education, the Constitution is required to be disclosed on the state's responsibility to ensure this right in the following terms referred to in art. 28: "Art 28 -. Education will respond to the public interest and will not serve individual and corporate interests. Universal access, retention, mobility and exit without discrimination and the requirement in the initial, basic and high school or equivalent level is guaranteed" The problem occurs when the lower-level rules, I mean the Law on Higher Education through its leveling system and regulates admission in his text several components for secure access of graduates to higher education, among ENES them (national examination for higher education), a mechanism that restricts, limits and prevents universal access to higher education for all students, because only those who pass this exam proving entitlement to access to higher education, which epitomizes a stage of vulnerability, inequality, injustice and discrimination. As provided Article 81 of the Organic Law on the subject, and Levelling System Admission is established, the same that controls admission to public institutions of higher education and the system regulated through Equalization and Admission, which shall be subject all applicants and students; likewise the Article 85 of the same law states that the Council of Higher Education shall establish policies and issue general rules to ensure transparency, fairness and equity in the Student Assessment System; This obviously creates a conflict between standards, the Constitution recognizes the right to unrestricted access to higher education and other Higher Education Act that prevents the effective exercise and enjoyment of this right; situation that must be remedied through a preliminary analysis of the legal reform issues will be the subject of research